Islamic Republic of Mauritania : Ex Post Assessment of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In this study, the ex post assessment (EPA) of longer program engagement with Mauritania is discussed. From this program, macroeconomic stability has been achieved. EPAs are intended to provide an opportunity to step back from continuing program relations to consider an analysis of the economic problems facing the country, review progress under IMF-supported programs, and draw forward-looking lessons for future IMF engagement. The newly designed poverty reduction strategy and ECF-supported program addresses the challenges identified by the EPA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet